Single-Molecule Electronics An Introduction to Synthesis, Measurement and Theory - Kiguchi, Manabu (Springer Nature Singapore : Imprint: Springer, 2016)
This book presents a multidisciplinary approach to single-molecule electronics. It includes a complete overview of the field, from the synthesis and design of molecular candidates to the prevalent experimental techniques, complemented by a detailed theoretical description. This all-inclusive strategy provides the reader with the much-needed perspective to fully understand the far-reaching ramifications of single-molecule electronics. In addition, a number of state-of-the-art topics are discussed, including single-molecule spectro-electrical methods, electrochemical DNA sequencing technology, and single-molecule chemical reactions. As a result of this integrative effort, this publication may be used as an introductory textbook to both graduate and advanced undergraduate students, as well as researchers with interests in single-molecule electronics, organic electronics, surface science, and nanoscience. .